2014
DOI: 10.1016/j.procs.2014.05.510
|View full text |Cite
|
Sign up to set email alerts
|

A Lightweight Middleware Platform for Distributed Computing on Wireless Sensor Networks

Abstract: The peculiar features of Wireless Sensor Networks (WSNs) suggest to exploit the distributed computing paradigm to perform complex tasks in a collaborative manner, in order to overcome the constraints related to sensor nodes limited capabilities. In this context, we describe a lightweight middleware platform to support the development of distributed applications on WSNs. The platform provides just a minimal general-purpose software layer, while the application components, including communication and processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…On the receiver side the payload is interpreted as if it had been typed at the command line interface. We exploited this feature in the implementation of a Timing-Sync protocol [5], and to remotely program deployed nodes in an interactive manner through a command line interface [6].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the receiver side the payload is interpreted as if it had been typed at the command line interface. We exploited this feature in the implementation of a Timing-Sync protocol [5], and to remotely program deployed nodes in an interactive manner through a command line interface [6].…”
Section: Methodsmentioning
confidence: 99%
“…As an added consequence re-uploads of the application code could not be excluded should the hardware-abstraction layer require modifications. In some previous works we showed that programming WSNs with an extensible high-level language without compromising code execution efficiency is feasible by adopting a programming methodology based on Forth and we introduced a lightweight middleware for WSNs based on it [5], [6]. In this paper we show how our middleware can be easily extended with the ability to process symbolic data.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In [10], the authors described the outlook of middleware for wireless sensor networks. Authors in [15] designed and implemented a lightweight middleware platform for distributed computation on wireless sensor networks. As wireless sensor network is becoming a new paradigm [16] in the realm of Internet of Everything, some studies have been made on facilities virtualization.…”
Section: Related Workmentioning
confidence: 99%